Gambaran Pelari Pada Event Pocari Sweat Run Tahun 2022 - Bagus Tri Budi Antoro; Andika Bayu Putro (Universitas Negeri Surabaya, 2024)
Background: One of the sporting events that is currently popular is running. Running events are increasingly mushrooming in various cities in Indonesia, both on a local, national and even international scale. Pocari sweat run Indonesia 2022 is entering its ninth year, this time being held in Bandung City, the capital of West Java Province, on the week of July 24 2022. Methods: This research uses a quantitative descriptive approach. The number of running participants was 4355 people, divided into 3 categories, full marathon, half marathon and 10 km run. All data are presented as mean ± SD, minimum value and maximum value.. Results: The results of the study were that most half marathon and 10km runners were aged ≤40 years. More women take part in running competitions in the 10km category. Participants running the full marathon, with the fastest finishing time at 14.36 WIB, for half marathoners aged ≤40 years, with the fastest time at 13.10 WIB. At age >40 years, the fastest time for the half marathon was 13.27 WIB, the 10 km category was based on age group, where age ≤40 years, the participant with the fastest finish time finished the race at 12.32 WIB. At the age of >40 years, the participant with the fastest time was 12.40 WIB. Conclusions: Running participants are dominated by men, most aged <40 years. The 10km and half marathon categories are the categories with the highest number of enthusiasts compared to the full marathon. One of the findings in this research is the need for special attention to women's participation, especially in running events.